Anti-angiogenic effect of curcumin, curcumin ethylenediamine derivative and curcumin ethylenediamine manganese complex - Leena Suntornsuk (2018)
We investigated the anti-angiogenic effect of curcumin, curcumin ethylenediamine derivative (curcumin ED) and curcumin ethylenediamine manganese complex (curcumin EDMn) through the inhibition of the formation of tube-like structures by human umbilical vascular endothelial cells (HUVEC). Curcumin, curcumin ED, curcumin EDMn did not show cytotoxicity to HUVEC at concentrations equal and lower than 10 μM. At the concentration of 10 μM, curcumin, curcumin ED and curcumin EDMn inhibited the tube formation by approximately 94%, 40% and 65%, respectively. These results suggest that curcumin ED and curcumin EDMn might be useful as anti-angiogenic drugs in addition to their anti-lipid peroxidase and superoxide dismutase activities as described in our previous studies. © 2004, Medical and Pharmaceutical Society for WAKAN-YAKU. All rights reserved.